Behavioral Own-Body-Transformations in Children and Adolescents With Typical Development, Autism Spectrum Disorder, and Developmental Coordination Disorder - Gauthier, Soizic; Anzalone, Salvatore M.; Cohen, David; Zaoui, Mohamed; Chetouani, Mohamed; Villa, François; Berthoz, Alain; Xavier, Jean (Frontiers in Psychology, 2018)
Background: In motor imitation, taking a partner’s perspective often involves a mental body transformation from an embodied, ego-centered viewpoint, to a disembodied, hetero-centered viewpoint. Impairments of both own-body-transformation (OBT) and abnormalities in visual spatial processing have been reported in patients with neurodevelopmental disorders including autism spectrum disorder (ASD). In the context of a visual-motor interactive task, studying OBT impairments while disentangling the contribution of visual spatial impairments associated with motor coordination problems has not been investigated. Methods: 85 children and adolescents (39 controls with typical development, TD; 29 patients with ASD; 17 patients with developmental coordination disorder, DCD), aged 6 to 19 years, participated in a behavioral paradigm in which participants interacted with a virtual tightrope walker (TW) standing and moving with him. The protocol enables to distinguish ego-centered and hetero-centered perspectives. Results: We show that (1) OBT was possible but difficult for children with neurodevelopmental disorders, as well as for TD children, when the task required the participant to perform a mental rotation in order to adopt a hetero-centered perspective (2) Using multivariate models, hetero-centered perspective score was significantly associated with age, TW orientation, latency and diagnosis. ASD and TD group’s performances were close and significantly correlated with age. It was not the case for DCD specifically handicapped by visual spatial impairments. (3) ASD and DCD did not perform similarly: motor performance as shown by movement amplitude was better in DCD than ASD. ASD motor response were more ambiguous and hardly readable. Conclusion: Changing perspective in a spatial environment is possible for patients with ASD although delayed compared with TD children. In patients with DCD their visual spatial impairments negatively modulated performances in the experiment.